The Use of Coal Fossil Energy of Mashlahah Perspective and Hifdz al-Nafs al-Ghazali Principles - Aufi, Ahmad Umam; Maghfiroh, Maila Shofa (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The need for energy for human life is a very natural thing. Energy is very closely related to human survival. However, the choice to use energy is in the hands of humans. This paper aims to examine the use of coal for fossil energy from the perspective of al-Ghazali's mashlahah. This research is a literature review that uses the Islamic legal philosophy approach to portray the use of coal. Data is gathered from various studies and surveys and analyzed through the lens of Mashallah al-Ghazali. The results of this study state that the maintenance of the right to life and the preservation of human life cannot be negotiated at any price. Coal and fossil fuel energy, although they have commercial value, boost economic growth, and promote people's welfare, have ecological impacts that pose threats to human survival. The use of coal as a fossil fuel is not in line with al-Ghazali's three levels of mashlahah, namely dharuriyah, hajiyah, and tahsinihyah. Renewable energy is seen as a viable alternative to fossil coal energy in reducing the impact of mafsadat, which endangers human life.